SWOT Analysis in Skincare Product Marketing Strategy Efforts to Build Competitive Opportunities of PT. XYZ - Zulva, Azka Fatihatuz (Siber International Journal of Education Technology (SIJET), 2025)
The purpose of this study was to create a successful long-term competitive strategy for PT XYZ, a company engaged in the production and distribution of skin care products. Companies face great difficulties in maintaining competitiveness amid increasingly fierce market competition, changing consumer preferences, and accelerating technological advancements. This study identifies internal (strengths and weaknesses) and external (opportunities and threats) factors that affect business performance and strategy by using a descriptive qualitative approach based on literature studies and SWOT analysis. The results of the analysis show that PT XYZ has strengths in well-known brands, product diversity, and consumer loyalty, but also has weaknesses in labor skills, market segmentation, and product pricing. The growth of e-commerce, customer loyalty, and skincare trends as staples are opportunities, while the abundance of competitors, fluctuations in raw material prices, and rapid technological advancements are major threats. In response to this situation, SO, WO, ST, and WT strategies are implemented by prioritizing digitalization optimization, product innovation, and human resource improvement. It is hoped that the strategy made will increase PT XYZ's competitiveness and sustainability in the national and international markets.